Awareness of physicians and dentists in Serbia about the association between periodontitis and systemic diseases: a cross-sectional study - Marija Stojilković; Ivana Gušić; Dušan Prodanović; Miloš Ilić; Nevena Pecikozić; Tanja Veljović; Jelena Mirnić; Milanko Đurić (BMC, 2023)
Abstract Background Strong evidence supports the association between periodontitis and certain systemic diseases. The aim of the present study was to evaluate the knowledge of a group of physicians and dentists in Serbia regarding this topic and assess their professional actions to prevent and control both periodontal and systemic diseases. Methods An anonymous self-administered structured questionnaire was sent to the available e-mail addresses of randomly selected healthcare providers working in Serbia. According to the inclusion criteria, general practitioners, specialists, general dentists, and specialists working in government hospitals and private practices in various cities in Serbia were recruited in the study. The questionnaire consisted of 17 questions divided into three parts. The first part recorded the sociodemographic characteristics of participants, the second part included questions about the clinical manifestation and etiology of periodontitis, as well as knowledge of the association between periodontitis and systemic diseases, and the third part included questions about professional procedures for the prevention and control of periodontitis and systemic diseases. Results A total of 1301 health participants, 739 (57.8%) physicians and 562 (43.2%) dentists, were included in this cross-sectional study. Most respondents (94.7%) were aware of the association between periodontitis and general health. The highest percentage of respondents associated diabetes mellitus and periodontitis. Factors significantly associated with higher knowledge were female sex (odds ratio [OR], 1.86; 95% confidence interval [CI], 1.37-2.52; p < 0.001) and dental profession (OR, 5.86; 95% CI], 4.03-8.53; p < 0.001). Participants who had higher knowledge score were more likely to ask their patients about gum/systematic health (p < 0.001) and refer them to dentists/physicians (p < 0.001). Conclusions It was concluded that compared to the group of dentists, the group of physicians had less knowledge of the relationship between periodontitis and systemic diseases. The female gender was significantly associated with better knowledge. A better understanding of this topic is associated with better clinical practice.